P21 activated kinase 6: a promising tool for predicting small cell lung cancer diagnosis and treatment response - Chen,Simei; Han,Kexin; Chen,Yinyi; Wei,Liping; Sun,Xinlu; Luo,Yi; Wen,Lili; Tan,Liming (PeerJ, 2025)
Objective Building upon the established role of P21 Activated Kinase 6 (PAK6) in tumor progression and chemoresistance pathways, we postulate its potential as a dual-function biomarker for small cell lung cancer (SCLC). This investigation aims to conduct a comprehensive evaluation of PAK6’s diagnostic validity and prognostic significance through comparative analysis of PAK6 serological levels across distinct clinical cohorts to determine diagnostic thresholds, and its clinical correlation with therapeutic responsiveness. Patients and Methods This study included 109 patients diagnosed with SCLC, 92 patients with non-small cell lung cancer (NSCLC), 85 patients with pulmonary nodules (PN), and 94 healthy individuals undergoing routine physical examinations as the normal control group (NC). Serum PAK6 concentrations were measured using enzyme-linked immunosorbent assay (ELISA). Additionally, levels of neuron-specific enolase (NSE), carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA19-9), and pro-gastrin-releasing peptide (ProGRP) were quantified via chemiluminescence assays. Progression-free survival (PFS) data for SCLC patients were collected through case review and telephone follow-up. Results Serum PAK6 levels were significantly higher in the SCLC group compared to the other three groups (p < 0.01). Similarly, NSE and ProGRP levels were markedly elevated in the SCLC group compared to the other groups (p < 0.01). Correlation analysis revealed a positive association between PAK6 and variables such as gender, VA (Veteran’s Administration Lung Cancer Study Group) stage, age, smoking status, CEA, CA19-9, NSE, and ProGRP. The serum tumor markers (STMs) PAK6, NSE, and ProGRP exhibited superior diagnostic performance, with AUCs of 0.892, 0.834, and 0.935, respectively (95% confidence interval (CI) [0.857–0.927], [0.778–0.890], and [0.909–0.960]), compared to CEA and CA19-9 (AUCs = 0.676 and 0.611, respectively; 95% CI [0.622–0.731] and [0.547–0.675]) (p < 0.01). Furthermore, PAK6, NSE, and ProGRP levels significantly decreased after three months of treatment, while CEA and CA19-9 showed no significant changes. Survival analysis demonstrated that higher PAK6 levels were associated with poorer SCLC prognosis. Increased serum PAK6 expression correlated with shorter PFS (HR = 2.02 [1.33–3.07], P = 0.001). Conclusion Serum PAK6 holds significant clinical value for the diagnosis, treatment monitoring, and prognosis evaluation of SCLC and may serve as a potential therapeutic target for the disease.
Keywords: PAK6; Small cell lung cancer; Serum tumor markers; ProGRP; NSE